Do comets C/1861 G1 (Thatcher) and C/1861 J1 (Great Comet) have a common origin? - Branham, Richard Lacy (2015)
A new orbit is calculated for Comet C/1861 G1 (Thatcher), associated withthe Lyrid meteor shower, to replace Oppolzer?s orbit of 1864. The new orbit is basedupon 649 observations, 326 in right ascension and 323 in declination, made between11 April 1861 and 7 Sept. 1861. The final orbit uses residuals calculated with theWelsch weighting function. The comet?s period of 416.87 ± 0.56 yr agrees withOppolzer?s period of 415 yr athough other elements such as the inclination differ.Although the post-perihelion residuals are relatively random, 52.1% probability ofrandomness, pre-perihelion residuals lack randomness indicating possible deviationsfrom Keplerian motion caused by ejection of meteoritic material. Comet Thatcheris unrelated to the Great comet of 1861.